Three-dimensional CoM energetics, pelvis and lower limbs joint kinematics of uphill treadmill running at high speed. Issue 5 (3rd March 2020) - Okudaira, Masamichi; Willwacher, Steffen; Kuki, Seita; Yamada, Kaito; Yoshida, Takuya; Tanigawa, Satoru
ABSTRACT: The purpose of this study was to investigate the effects of slope on three-dimensional running kinematics at high speed. Thirteen male sprinters ran at high speed (7.5 m/s) on a motorised treadmill in each a level and a 5.0% slope condition. Three-dimensional motion analysis was conducted to compare centre of mass (CoM) energetics, pelvis segment and lower limb joints kinematics. We found that contact time was not affected by the slope, whereas flight time and step length were significantly shorter in uphill compared to level running. Uphill running reduced negative CoM work and increased positive CoM work compared to level running. Ankle, knee and hip joints were more flexed at initial ground contact, but only the knee was more extended at the end of stance in uphill compared to level running. Additionally, the hip joint was more abducted, and the free leg side of the pelvis was more elevated at the end of stance in uphill running. Our results demonstrate that joint motion must be developed from a more flexed/adducted position at initial contact through a greater range of motion compared to level running in order to meet the greater positive CoM work requirements in uphill running at high speed.